2016
DOI: 10.1002/med.21427
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry, Pharmacology, and Clinical Implications of TRPV1 Receptor Antagonists

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is an ion channel expressed on sensory neurons triggering an influx of cations. TRPV1 receptors function as homotetramers responsive to heat, proinflammatory substances, lipoxygenase products, resiniferatoxin, endocannabinoids, protons, and peptide toxins. Its phosphorylation increases sensitivity to both chemical and thermal stimuli, while desensitization involves a calcium-dependent mechanism resulting in receptor dephosphorylation. TRPV1 functions as a sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 282 publications
(334 reference statements)
2
58
0
1
Order By: Relevance
“…Transient receptor potential vanilloid type 1 (TRPV1) is a ligand-gated nonselective cation channel and member of the vanilloid TRP family. In the chromosome 17p13 is located the Trpv1 gene, which encodes a 95-kDa protein containing 839 amino acid residues [364]. TRPV1 has six transmembrane domains (TM), presenting a pore region located between TM5 and TM6 domains.…”
Section: Transient Receptor Potential Vanilloid Type 1 (Trpv1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Transient receptor potential vanilloid type 1 (TRPV1) is a ligand-gated nonselective cation channel and member of the vanilloid TRP family. In the chromosome 17p13 is located the Trpv1 gene, which encodes a 95-kDa protein containing 839 amino acid residues [364]. TRPV1 has six transmembrane domains (TM), presenting a pore region located between TM5 and TM6 domains.…”
Section: Transient Receptor Potential Vanilloid Type 1 (Trpv1)mentioning
confidence: 99%
“…TRPV1 has six transmembrane domains (TM), presenting a pore region located between TM5 and TM6 domains. The N-terminal tail allows binding of calmodulin and ATP to modulate TRPV1 activation while C-terminus contains a TRP domain and binding sites for phosphatidylinositol 4,5-bisphosphate (PIP2) and calmodulin [364].…”
Section: Transient Receptor Potential Vanilloid Type 1 (Trpv1)mentioning
confidence: 99%
See 1 more Smart Citation
“…From a pharmacological perspective, the research carried out so far has shown that capsaicinoids, particularly capsaicin, have a diversity of biological and physiological functions in vitro, so they play roles as antioxidants, stimulants of the energetic metabolism, fat accumulating suppressors, anti-inflammatories, neurostimulants and apoptosis-alleviating agents in neurodegenerative disorders [ 20 , 28 , 29 , 30 ]. Regarding the mechanism of action, capsaicinoids act on a family of ion channels known as transient receptor potential (TRP) channels which, in mammals, are framed within the subtype TRP Vanilloid (TRPV1) [ 31 , 32 ]. It has been also found that in many types of cancers, the proapoptotic activity of capsaicin is also mediated by this TRPV, and the activation of the p53 tumor suppressing protein by a phosphorylation process is induced by capsaicin [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that selective sensory neuropathy can be induced by systemic capsaicin-induced desensitization. Systemic capsaicin treatment at appropriate doses induces a selective impairment of C-fiber primary sensory neurons expressing the capsaicin receptor TRPV1 [99,100,101]; which can be observed by, e.g., depletion of cardiac CGRP-containing afferent nerves [11]. Systemic capsaicin-desensitized animals have elevated chemical and heat pain thresholds, show no signs of pain, irritation or discomfort, and behave similar to controls [102].…”
Section: Methodsmentioning
confidence: 99%